“Step up!” A mobile application to promote an eco-friendly lifestyle - Lee, Ryan Jun Whai (Nanyang Technological University, 2024)
With the rising threat of ecological collapse, there is a need for urgent action. Combining the widespread adoption of smartphones and mobile technology, this project seeks to foster sustainable behaviours and engage individuals in the fight against environmental challenges. The mobile application “Step Up!” aims to promote sustainability by encouraging users to participate in eco-friendly challenges such as reducing waste, conserving energy, and supporting green initiatives. By using a challenge-tracking system and integrating points-based rewards, users are incentivized to adopt and maintain sustainable habits. In this report, the development of “Step Up!”, a mobile application that fosters sustainable living practices in Singapore is documented and discussed. Technologies such as Android Studio, Google Firebase, Java and XML are to be utilized.